C3-Functionalized Benzothiophene Sulfone Derivatives: Synthesis and Antimicrobial Evaluation - Tariq Ahmed Gnaidi; Abrar Meeloud Alsunousi; Bushray Ayman Alajnaf; Naseeb Mohammad Alsalih; Nour Fathi Salim; Saji Khlid Shohoub (African Journal of Advanced Pure and Applied Sciences, 2025)
This study presents a strategic synthetic approach to functionalize the traditionally unreactive C3 position of the benzothiophene core. A series of 3-chloro-N-(aryl)benzo[b]thiophene-2-carboxamides (2a–d) were synthesized in good to excellent yields (53–83%) via amidation of 3-chloro-2-chlorocarbonylbenzo[b]thiophene (1). Subsequent oxidation with hydrogen peroxide in acetic acid afforded the corresponding sulfone derivatives (3a–d), a transformation that reduced aromaticity and activated the C3 position. This activation enabled a nucleophilic aromatic substitution, where chlorine in sulfone 3b was replaced by ethylamine, isopropylamine, and diethylamine, yielding novel 3-aminobenzothiophene-1,1-dioxides (4a–c) in moderate yields (50–64%). All new compounds were fully characterized by IR, ¹H NMR, and ¹³C NMR spectroscopy. The synthesized derivatives were evaluated in vitro for antimicrobial activity against Gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis), Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa), and fungal strains (Candida albicans, Crysosporium pannical, Aspergillus niger, Rhizopus oryzae). While overall activities were slight to moderate compared with standard drugs, compounds 3a and 3b displayed a promising broad-spectrum profile.These findings establish an efficient and versatile methodology for accessing C3-functionalized benzothiophenes, providing a valuable foundation for the design of new lead structures against resistant microbes.